A Web-Based Psychosocial Intervention for Family Caregivers of Older People: Results from a Mixed-Methods Study in Three European Countries - Barbabella, Francesco; Poli, Arianna; Andréasson, Frida; Salzmann, Benjamin; Papa, Roberta; Hanson, Elizabeth; Efthymiou, Areti; Döhner, Hanneli; Lancioni, Cristina; Civerchia, Patrizia; Lamura, Giovanni (My University, 2016)
Background: Informal caregiving is the main source of care for older people in Europe. An enormous amount of responsibility and care activity is on the shoulders of family caregivers, who might experience problems in their psychological well-being and in reconciling caregiving and their personal sphere. In order to alleviate such burden, there is increasing interest and growing research in Europe on Web-based support addressing family caregivers and their needs. However, the level of development and penetration of innovative Web-based services for caregivers is still quite low and the access to traditional face-to-face services can be problematic for logistic, availability, and quality reasons. Objective: As part of the European project INNOVAGE, a pilot study was conducted for developing and testing a Web-based psychosocial intervention aimed at empowering family caregivers of older people in Italy, Sweden, and Germany. The program offered information resources and interactive services to enable both professional and peer support. Methods: A mixed-methods, sequential explanatory design was adopted. Caregivers' psychological well-being, perceived negative and positive aspects of caregiving, and social support received were assessed before and after the 3-month intervention. Poststudy, a subsample of users participated in focus groups to assist in the interpretation of the quantitative results. Results: A total of 94 out of 118 family caregivers (79.7%) from the three countries used the Web platform at least once. The information resources were used to different extents in each country, with Italian users having the lowest median number of visits (5, interquartile range [IQR] 2-8), whereas German users had the highest number (17, IQR 7-66) (P<.001). The interactive services most frequently accessed (more than 12 times) in all countries were the social network (29/73, 40%) and private messages (27/73, 37%). The pretest-posttest analysis revealed some changes, particularly the slight worsening of perceived positive values of caregiving (Carers of Older People in Europe [COPE] positive value subscale: P=.02) and social support received (COPE quality-of-support subscale: P=.02; Multidimensional Scale of Perceived Social Support subscale: P=.04), in all cases with small effect size (r range -.15 to -.18). Focus groups were conducted with 20 family caregivers and the content analysis of discussions identified five main themes: online social support, role awareness, caregiving activities, psychological well-being, and technical concerns. The analysis suggested the intervention was useful and appropriate, also stimulating a better self-efficacy and reappraisal of the caregivers' role. Conclusions: The intervention seemed to contribute to the improvement of family caregivers' awareness, efficacy, and empowerment, which in turn may lead to a better self-recognition of their own needs and improved efforts for developing and accessing coping resources. A major implication of the study was the finalization and implementation of the InformCare Web platform in 27 European countries, now publicly accessible (www.eurocarers.org/informcare).
Keywords: Internet; Caregivers; Frail elderly; Health education; Social networking; Social support